Effect of Two Local Chemical Fertilizers on Biomass and Chlorophyll A Content of the Cyanobacteria “Anabaena Oryzae” Isolated From Paddy Fields - Annie F. D’souza E. Gomes (International Journal of Control and Automation, 2021)
Cyanobacteria forms a large group of structurally complex and ecologically significant gram negative prokaryotes which flourish in rice fields and also known to sustain the fertility of this ecosystem. This study is aimed to study the effect of locally used fertilizers on indigenous species of BGA selected from rice field areas in Goa. The indigenous dominant heterocyst tous cyanobacteria were selected from local rice fields. The most dominant forms were Anabaena oryzae Fritsch. The cyanobacteria were treated with local fertilizers with known chemical compositions to study the effect on biomass and chlorophyll a content. It was seen that the fertilizers do not have any detrimental effect on growth of Anabaena oryzae. Statistical analyses showed significance, It was seen that at all concentration, cyanobacteria showed stimulatory growth as seen by increase in biomass, chlorophyll’a’ content.